Challenges of urban space for sustainable solid waste management in the Langat Basin, Malaysia - Ahmad Fariz Mohamed; Shaharudin Idrus; Abdul Samad Hadi (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
Urbanization process in the Langat Basin, Malaysia, grow rapidly for the past three decades. The land use change urban areas of the basin increased from 2.3% in 1974 to 32% in 2010. While the population experiencing rapid growth from 665,395 in 1991 and increase to 1,492,422 in 2015. The vibrancy of economic activities with increasing of population, leads to increasing generation of solid waste in the basin. Solid waste generation increased from 332.7 ton/day in 1991 and increased to 1,641 ton/day in 2015. The current practice of waste management in the Langat Basin still focus on disposals to landfill. Previously there are nine landfill supporting the needs of the basin, however there are only three landfill left. The landfills closed were due to pressure from the development of residential, commercial and industrial areas. The demand for new landfill will compete for space with other economic activities and security of ecosystem services. Land are so precious, thus priorities will not be given for landfill in the Langat Basin. Hence there is a need for change of waste management. Priority should be given to resource recovery with waste recycling, waste reduction and waste reuse as the main approach, with support of other strategic plan such as designing product and system as well as using incinerator to ensure reduction of solid waste flow to landfill. These approaches and strategies will able to reduce dependency of space for new landfill in the Langat Basin in the future.